Gastric cancer prevention strategies: A global perspective - Eusebi, Leonardo Henry; Telese, Andrea; Marasco, Giovanni; Bazzoli, Franco; Zagari, Rocco Maurizio (Journal of gastroenterology and hepatology, 2020)
Gastric cancer (GC) is the fifth most common cancer worldwide, and mortality rates are still high. Primary preventive strategies, aimed to reduce risk factors and promote protective ones, will lead to a decrease in GC incidence. Helicobacter pylori infection is a well‐established carcinogen for GC, and its eradication is recommended as the best strategy for the primary prevention. However, the role of other factors such as lifestyle, diet, and drug use is still under debate in GC carcinogenesis. Unfortunately, most patients with GC are diagnosed at late stages when treatment is often ineffective. Neoplastic transformation of the gastric mucosa is a multistep process, and appropriate diagnosis and management of preneoplastic conditions can reduce GC‐related mortality. Several screening strategies in relation to GC incidence have been proposed in order to detect neoplastic lesions at early stages. The efficacy of screening strategies in reducing GC mortality needs to be confirmed. This review provides an overview of current international guidelines and recent literature on primary and secondary prevention strategies for GC.